Turn off your engine: Reducing idling amongst professional truck drivers - Sigridur Soffia Sigurjonsdottir; Aud Kielland Elnes; Kalliu Carvalho Couto (Transportation Research Interdisciplinary Perspectives, 2022)
Road transportation is the third largest contributor to nitrogen oxide (NOx) emissions in Norway. Norwegian authorities are working toward replacing current fleet vehicles with zero-emission technologies. Altering driving habits can also contribute up to a 25 % reduction of fuel consumption. The present study reports findings of a behavioral intervention that sought to reduce engine idling among eight professional drivers of biodiesel fueled trucks. Each component was implemented separately. The components included information about the intervention, delayed feedback on idling time (group and individual), and instructions about efficient driving behavior. An 8.6 % reduction in the groups idling was observed. Effect sizes revealed a significant overall decrease in idling (Tau = 0.63, p < 0.01), with variations of which component affected each driver’s behavior the most. In addition, the fuel use was reduced by 6.6 %. The results suggest that multicomponent interventions may be a viable alternative to reduce idling, but further research on variable effects of individual components is recommended. In addition to a replication with a larger group.